Patterns of Interaction among Mono-Cultural English as Second Language Learners - Arumugam, Nalini; Mello, Geraldina de; Muthusamy, Indrani (EDUCARE, 2011)
ABSTRACT: By exploring the educational pedagogies and classroom discourses, it is the aim of the paper to extend theoretical insights into the way ESL (English as Second Language) writing classrooms might help to make over, negotiate, and manage the linguistic, social and learning idenÂtities of the mono-cultural learners in the classrooms. The basic premise of social interdependence theory is that the way interdependence among goals is structured determines how individuals interact, which in turn largely determines outcomes. Research, therefore, has focused on studentâstudent interaction in ESL tertiary writing classroom in an institution of higher learning. The results indicated that mono-cultural learners in an ESL classroom juxtaposed two languages (L1 and L2) and appropriated their bilingualism to learn English language. The results also revealed that group discussions in ESL classrooms in institution of higher learning offered Â experiential learning whereby learners became more skilled to use suitable choice of words Â (at times with help of their more capable peers), specifically utilising their bilingual expertise. The end results of this study point out a favourable feature of the discourses of the ESL learners striving for mutual benefits to successfully complete the assigned tasks. KEY WORDS: Mono-cultural, English as second language, face-to-face interaction, patterns of interaction, and Malay students. About the Authors: Dr. Nalini Arumugam, Geraldina de Mello and Indrani Muthusamy are Lecturers at the Academy of Language Studies UiTM (MARA Technology University), Melaka Campus, KM 26, Jalan Lendu, 78000 Melaka, Malaysia. They can be reached at: nalini@melaka.uitm.edu.my, geraldine@melaka.uitm.edu.my, and indrani@melaka.uitm.edu.myHow to cite this article? Arumugam, Nalini, Geraldina de Mello & Indrani Muthusamy. (2011). âPatterns of Interaction among Mono-Cultural English as Second Language Learnersâ in EDUCARE: International Journal for Educational Studies, Vol.4(1) August, pp.11-26. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 5, 2011); Revised (July 9, 2011); and Published (August 17, 2011).